A note on the two-input arc elasticity of substitution - Vázquez, Andrés (Estudios Económicos de El Colegio de México, 2008)
This note suggests a measure for the two-input arc elasticity of substitution that comes up naturally and preserves the salient characteristic of the Hicks-Robinson original concept. In particular, (i) it gives the average value of point substitution elasticities over the logarithmic arc of the input price ratio, and leads therefore to the exact estimation of the CES production function family, and (ii) its relationships with the discrete change in factor shares are formally parallel to those well known for the point elasticity assumption.